Greenpeace Campaigns Against Asia Pulp & Paper and Wilmar International: A Comparative Research - Sitorus, Syifa Adzraa; Purnama, Chandra (Global Strategis, 2023)
As an International Non-Governmental Organization (INGO), for years, Greenpeace has waged campaigns against rainforest deforestation in Indonesia by multinational corporations, such as Asia Pulp & Paper and Wilmar International, the top players in their respective industries. This study reviews the similarities and differences in campaign strategies used by Greenpeace against APP and Wilmar while showing the process of global media communication. The research was conducted as a comparative study using qualitative methods based on the Sandman Environmental Communication Model. Data collected from documents and audio-visual materials passed through a triangulation process to cross-check its interpretation. Eventually, this research finds that Greenpeace relied on the image of well-loved characters like Barbie to create intrigue in its "Barbie, It's Over” campaign against Mattel and, in turn, APP. While with Wilmar, Greenpeace took a more sympathetic approach using a baby orangutan character in the "Rang-tan” video. Both align with the Sandman Model: relying on publicity stunts to stimulate independent information-seeking from the communicant, which in turn will change their behaviour. Greenpeace's campaign strategy described in this study can be an example for other civil society organizations to achieve sustainable positive behaviour change. Keywords: Asia Pulp & Paper; global media communication; Greenpeace; international environmental campaign; Wilmar International   Selama bertahun-tahun, Greenpeace sebagai Organisasi Non-Pemerintah Internasional (INGO) melakukan kampanye melawan deforestasi hutan hujan di Indonesia oleh perusahaan multinasional seperti Asia Pulp & Paper (APP) dan Wilmar International yang merupakan pemain utama di industri masing-masing. Penelitian ini mengkaji persamaan dan perbedaan strategi kampanye yang digunakan Greenpeace terhadap APP dan Wilmar serta menjelaskan proses komunikasi media global yang terjadi. Penelitian ini dilakukan sebagai studi komparatif menggunakan metode kualitatif berdasarkan Model Komunikasi Lingkungan Sandman. Data dikumpulkan melalui studi dokumen dan bahan audio visual yang melewati proses triangulasi untuk memeriksa silang interpretasi data. Temuan utama penelitian ini lantas adalah bahwa Greenpeace mengandalkan citra karakter yang dicintai publik seperti Barbie untuk menciptakan intrik dalam kampanye "Barbie, It's Over” melawan APP. Sementara dalam kampanye melawan Wilmar, Greenpeace mengambil pendekatan yang lebih simpatik dengan menggunakan karakter bayi orangutan dalam video "Rang-tan”. Keduanya sejalan dengan Model Sandman: mengandalkan aksi publisitas untuk merangsang pencarian informasi independen dari komunikan, yang pada gilirannya akan mengubah perilaku mereka. Strategi kampanye Greenpeace yang dijelaskan dalam studi ini pun dapat menjadi contoh bagi organisasi masyarakat sipil lainnya untuk mencapai perubahan perilaku positif yang berkelanjutan. Kata-kata kunci: Asia Pulp & Paper; Greenpeace; kampanye lingkungan internasional; komunikasi media global; Wilmar International